Concentration‐effect relationships of two infusion rates of the imidazoline antihypertensive agent rilmenidine for blood pressure and development of side‐effects in healthy subjects - De Visser, S. J.; Van Gerven, J. M. A.; Schoemaker, R. C.; Cohen, A. F. (British journal of clinical pharmacology, 2001)
Aims  The aim of this study was to compare the effect profiles of i.v. administered rilmenidine aimed at the same target plasma concentration, but attained with different rates. Methods  The study was placebo‐controlled, randomized, double‐blind, double‐dummy, three‐way, cross‐over in nine healthy volunteers. All subjects randomly received either a fast infusion, a slow infusion or a placebo infusion. The target concentration was set at 8 ng ml−1 with a fivefold difference in the time to reach the maximum concentration. Saccadic eye movements, electroencephalography (EEG), blood pressure and heart rate were measured every half hour. Drug plasma concentrations, adverse events, salivary flow and visual analogue scales were obtained every hour. Results  Changes in systolic/diastolic blood pressure at the end of the infusion were (mean ± s.d.) 13.3 ± 16.4/7.9 ± 7.5 mmHg with the fast infusion and 16.3 ± 12.7/10.2 ± 7.9 mmHg during the slow infusion, compared with 0.0 ± 13.2/1.3 ± 8.3 mmHg for the placebo occasion. Decrease of saccadic peak velocity (SPV) at the end of the infusion was 18.0 ± 5.2% during the fast infusion, 23.0 ± 7.0% with the slow infusion, and 6.1 ± 5.2% with placebo. PK/PD analysis showed similar concentration‐dependent linear reduction in SPV and blood pressure up to the maximum observed rilmenidine plasma level for both the fast and the slow infusion. Conclusions  The rate of infusion of rilmenidine in healthy volunteers does not influence the PK/PD relationship of saccadic eye movements and blood pressure up to the maximum observed rilmenidine plasma concentrations. Rilmenidine causes clear concentration‐dependent blood pressure reductions in healthy volunteers.